Retroviruses and Insights into Cancer - Dudley, Jaquelin; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Retroviruses cause chronic infections and insertion mutations in their hosts, often leading to the appearance of tumors. Studies of retrovirus-induced tumors have led to our understanding of many crucial concepts in cell and cancer biology, including the discoveries of reverse transcriptase, viral oncogenes, cellular proto-oncogenes and signal transduction pathways. This monograph provides an intriguing set of chapters on the many facets of retroviral involvement in cancers arising in a variety of organisms from fish to humans. Each chapter is written by experts in the field and relates recent work to previous experimental data. Retroviruses use many different mechanisms to induce cancers, ranging from activation of microRNAs, inactivation of tumor suppressor genes, activation or modifications of proto-oncogenes, as well as expression of viral proteins that manipulate cell signaling and the immune system. In recent years, retroviruses have been used as tools, not only for the characterization of cellular pathways, but also as vectors to deliver therapeutic or engineered genes. This knowledge is all the more startling due to the revelation that nearly 10% of the human genome consists of endogenous retroviruses, including many that are transcriptionally active. The emergence of new endogenous retroviruses causing lethal leukemias in koalas and, potentially, prostate cancer in humans ensures that the unique interactions of these viruses with their hosts will continue to fascinate and illuminate us.
1. Mouse mammary tumor virus -- 2. Jaagsiekte sheep retrovirus -- 3. Avian leukosis virus -- 4. Abelson murine leukemia virus -- 5. Human T-cell leukemia virus -- 6. Feline leukemia virus -- 7. Murine leukemia virus -- 8. Spleen focus-forming virus -- 9. Koala retrovirus -- 10. Human immunodeficiency virus.
Keywords: Medicine; Oncology; Microbiology; Medical virology; Biomedicine; Cancer Research; Virology; Medical Microbiology